Caracterização acústica e de imagens de ultrassonografia das vogais orais do português brasileiro - Svicero, Maria Augusta Forte (2012)
Studies on acoustic and articulatory phonetics reveal a possibility of understanding speech production through sound decomposing instrumentals (Acoustic Phonetics) and vocal tract imaging (Articulatory Phonetics). The acoustic theory of speech production provides an understanding of the adjustments made in the production of the vowel sounds of a language. Acoustic analysis and ultrasonography (US) enable, respectively, the description of acoustic and articulatory clues of the speech, by means of a non-invasive approach. The aim of this study was to present the acoustic description (formant frequencies) of oral vowels of Brazilian Portuguese (BP), São Paulo s variant, and present preliminary research data of vowels by images of US, pointing out possible acoustic-articulatory correlations. The first part of the data collection consisted on audio recording from 16 BP speakers, both genders, without speech, hearing or cranium-facial impairments or alteration. For the second part of the data collection, a male subject was submitted to simultaneous audio and US recordings. For this research a supporting device was developed to enable the transducer to be coupled to the US equipment. The recordings comprised the production of seven oral vowels of BP within the structure of the carrier sentences Diga [pVpV] baixinho (Say pVpv softly), where V is the oral vowel produced in stressed position and v post stressed position to the similar vowel. The acoustic recordings were digitized in .wav extensions and the F1, F2 and F3 measures were extraceted by means of software PRAAT. The US video samples were edited in order synchronize them to the audio data (software VideoPad Video Editor). The US images underwent two analysis approaches: 1st images were manually treated in order to retrieve the tongue contours 2nd - extraction of tongue displacement measures in vertical and horizontal axes. The acoustic data were statistically treated by means of discriminant analysis. The results pointed out that: (1) the formant frequency values contributed to the differentiation of the speech production s gender; (2) male F1 values were the most influential acoustic measures for the segregation of the seven oral vowels; (3) female F2 values were the most influential in the segregation of the seven oral vowels. US image data revealed the tongue body contour in the vertical and horizontal axis during the production of oral vowels of BP, suggesting better differentiation for displacements on the vertical axis. The reference values for the formant frequency of seven oral vowels of the male and female genders were presented, as well as images of US revealed potential application in study of acousticarticulatory for correlations vowels sounds